Early steps in the radiation of notoungulate mammals in southern South America: A new henricosborniid from the Eocene of Patagonia - Bauzá, Nicolás (2019)
Here we describe a new notoungulate mammal from the early Eocene (Itaboraian SALMA) of Chubut, Argentinian Patagonia, from the localities of Las Flores and Las Violetas Farm, represented by fragments of maxilla and isolated teeth. The specimens were found in the Las Flores Formation, Río Chico Group, and assigned to the Henricosborniidae, a primitive family within the order Notoungulata. Orome deepi gen. et. sp. nov. differs from other henricosborniids in a less developed metacone column in the upper molars, a larger metaloph in the third upper molar and a larger mean size. The morphometric analysis does not show any difference between the individuals of the two studied localities. The new addition to the henricosborniid diversity in Patagonia allows to provide a better understanding of the early radiation of notoungulates in South America.